Children’s behaviour and childhood obesity - Aus Ali; Osamah Al-ani; Faisal Al-ani (Pediatric Endocrinology, Diabetes and Metabolism)
Childhood obesity is a major complex and multifaceted public health challenge with significant short- and long-term health consequences. It is also associated with a significant reduction in quality of life and poorer mental health outcomes. In general, obesity occurs when energy intake exceeds energy expenditure. In children, however, the former can be interpreted as when a child has a body mass index (BMI) at or above the 95th percentile for children of the same age, sex, and ethnicity on growth charts. Obesity in children is influenced by a complex interplay of genetic, environmental, socio-economic, and behavioural factors. The relationship between a child's behaviour and childhood obesity is multifaceted and influenced by various factors, including dietary habits, physical activity levels, sedentary behaviours, family dynamics, socio-economic status, and environmental factors. Effective strategies for preventing and managing childhood obesity require a comprehensive, multi-sectoral approach that addresses individual, family, community, and educational institutes. Thus, addressing childhood obesity requires a comprehensive approach that addresses not only biological and environmental factors but also behavioural factors that influence children's eating behaviours, physical activity levels, sleep patterns, and emotional well-being. Early intervention and ongoing support are crucial for promoting healthy growth and development and reducing the burden of childhood obesity on individuals, families, and societies. This review discusses factors that influence the child’s behaviour and the relationship between the child’s behaviour and childhood obesity.